A Picture You Can Handle: Infants Treat Touch-Screen Images More Like Photographs than Objects - Ziemer, Christine J.; Snyder, Makenna (Frontiers in Psychology, 2016)
Infants actively explore their world in order to determine the different ways in which they can interact with various objects. Although research on infant perception has focused on how infants understand the differences between 2- and 3-dimensional objects, today’s infants increasingly encounter 2D images with interactive qualities on smart-phone screens, tablets, and laptops. The purpose of this experiment was to examine the types of manual behaviors infants direct towards tablet images and to compare these actions to those evoked by 2D photographs or 3D when tactile feedback is controlled. Infants between the ages of 7-10 months sat on their parent’s lap in front of a table with a built-in well covered by a clear, plastic sheet while the three types of displays (photographs, objects, and screen images on a tablet) were presented for 30 seconds each. Infants saw three examples of each type of display presented in the built-in well so that tactile feedback information from the different displays was controlled. Coders noted the proportion of trials in which infants grasped, scratched, rubbed, or patted the display. Results indicate that infants direct significantly more grasps, scratches, and rubs towards 3D objects than 2D photographs. Infants also direct more grasps to objects compared to screen images. Our data suggests that infants are treating screen images more similarly to 2D photographs than 3D objects.